SYSTEMS AND METHODS OF PHYSICAL EDUCATION NOWADAYS (Fiep Bulletin - online, 2014)
The evolution of Physical Education was historically associated with the human evolution, in the economic, cultural and social aspects. With the purpose of better understanding this development and relate it to the present moment, this work consist of a bibliografhic study that aims at presenting the influence that the European Methods of Physical Education exert on the Brazilian Physical Education nowadays. Such methods lie back to the 19th century: they intended to provide the regeneration of race, the promotion of health, besides improving the physical, moral an nationalistic capabilities. Both the German and Swedish methods, but mainly the Franch one exerted a great influence on the development of the Physical Education in Brazil that, even presenting a deepening in the scientific bases nowadays, seems it needs a large debate specially in the scholar and social levels so as to make it a constant, gradual and transforming practice.
Keywords: Physical Education; French Method; Swedish Method; Germain Method